Efektivitas UU TPKS Terhadap Pencegahan Kasus Kekerasan Seksual di Indonesia - Nihayah, Delfi; Sukmana, Oman (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2024)
Criminal Acts of Sexual Violence have begun to be widely discussed in small and national forums. In 2022, the government officially passed Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS). Unfortunately, the existence of this Law, which was made as a refinement of the previous Law, has not shown a significant impact on cases of sexual violence in Indonesia. This study was conducted to determine how the implementation and public understanding of the TPKS Law is, so that the effectiveness of the Law can be known. This research method is based on literature studies or library research which refers to textual documents such as important points about the TPKS Law, then data on the number of criminal acts of sexual violence calculated over the last two years, and information based on findings from previous studies. The findings from the review of journals, books and information from online media show that 6:4 of the Indonesian people are aware of the TPKS Law. However, most of them still do not understand how the Law is implemented.